Предмет: Алгебра,
автор: 8705354
2tgx - ctgx - 1=0
Как решить?
Ответы
Автор ответа:
0
2tgx - ctgx - 1 = 0
Можно сделать замену: tgx = t, тогда ctgx = 1/t, потому что ctgx функция обратная по отношению к функции tgx
2t - 1/t - 1 = 0
t₁ = -1/2
t₂ = 1
tgx = 1 ⇒ x = π/4 + π•n, n ∈ Ζ
tgx = -1/2 ⇒ x = -arctg(1/2) + π•k, k ∈ Ζ
Можно сделать замену: tgx = t, тогда ctgx = 1/t, потому что ctgx функция обратная по отношению к функции tgx
2t - 1/t - 1 = 0
t₁ = -1/2
t₂ = 1
tgx = 1 ⇒ x = π/4 + π•n, n ∈ Ζ
tgx = -1/2 ⇒ x = -arctg(1/2) + π•k, k ∈ Ζ
Похожие вопросы
Предмет: Информатика,
автор: Bonanchiktv
Предмет: Алгебра,
автор: ansvecov100
Предмет: Математика,
автор: zunisovazanel
Предмет: Физика,
автор: Vanillka
Предмет: История,
автор: katusha98